NO2-sensing proprieties of WS2/WO3 heterostructures obtained by hydrothermal treatment of tungsten oxide seed materials - Barbosa, Martin S.; Barbosa, Dirce N.O.; da Silva, Ranilson A. [UNESP]; Orlandi, Marcelo O. [UNESP] (Elsevier, 2023)
This work reports on the preparation of WS2/WO3 heterostructures for the development of nitrogen dioxide (NO2) sensors via a novel wet-chemical hydrothermal route approach. Different tungsten oxides were used as seed materials, and the heterostructure were formed using thioacetamide as a source of sulfur during a second hydrothermal treatment step. Structural and morphological characterizations demonstrated that the heterostructures can be described as WS2 nanosheets deposited over the tungsten oxide phase. Compared against the respective tungsten oxide seed materials, the heterostructures exhibited significant enhancement of the sensor response to NO2. High sensor signal to a 5 ppm exposure level was observed for the WS2/WO3 microplates at a working temperature of 200 °C, with good selectivity against reducing gases and a sub 2 ppm lower detection limit. To explain the enhancement of the sensor signal, we proposed an electronic sensitization mechanism based on the electronic barriers introduced by the p-n semiconductor junctions. Overall, this work introduces a low-cost, low-temperature, versatile wet-chemical synthetic route for the fabrication of transition metal dichalcogenide-metal oxide heterostructures with potential applications for the development of sensors capable of detecting NO2 at ppm levels.